Audit Komunikasi Strategi Digital Universitas Muhammadiyah Kotabumi dalam Menguatkan Brand Image di Instagram - Della Monica Della; Devi Wening Astari; Rizky Rahmanda Irawan; Novekawati (Komsospol, 2023)
The fast-growing technology on social media has changed the behavior of the public in receiving information. Today's social media use in Indonesia is growing so rapidly every year. According to Melansir Data Reportal, by 2023, there are 167 million social media users out of 153 million over the age of 18, which is 79.5% of the total population. The purpose of this research is to analyze the effectiveness of digital branding and positioning strategies carried out by the University of Muhammadiyah Kotabumi with the approach of auditing communication using the method of SOSTAC. The results of this study show that the University has not yet had a field of human rights, so UMKO's identity is not maximum, branding, and postitoning are not well managed and the use of social media especially Instagram is not maximal even can be passively regulated.